2008
DOI: 10.1287/orsc.1080.0398
|View full text |Cite
|
Sign up to set email alerts
|

Perspective—Making Doubt Generative: Rethinking the Role of Doubt in the Research Process

Abstract: In this paper, we want to shift the attention of our scholarly community to the living condition of doubt and its underappreciated significance for the theorizing process. Drawing on Peirce's notion of abduction, we articulate the relationship between doubt and belief in the everyday imaginative work central to theorizing, and establish the role played by doubt as abduction's engine in these efforts. We propose three strategic principles for engaging and using doubt in the research process. In concluding, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
413
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(415 citation statements)
references
References 37 publications
0
413
0
2
Order By: Relevance
“…Doubt and the questioning arising from it thus appear to be crucial for exploring one's general beliefs about knowledge and knowing (DeBacker & Crowson, 2006). We therefore adopt Locke et al's (2008) notion of doubt-the experience of not knowing-to depict this raw epistemological competence driving reflective questioning at the individual level (cf. King & Kitchener, 1994;Ertmer & Newby, 1996).…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Doubt and the questioning arising from it thus appear to be crucial for exploring one's general beliefs about knowledge and knowing (DeBacker & Crowson, 2006). We therefore adopt Locke et al's (2008) notion of doubt-the experience of not knowing-to depict this raw epistemological competence driving reflective questioning at the individual level (cf. King & Kitchener, 1994;Ertmer & Newby, 1996).…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
“…Suggesting here means introducing new ideas (cf. abduction as defined by Peirce) (Burks, 1946;Locke et al, 2008), based on previous observations. Intellectualizing involves making inferences by combining inductive premises.…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
“…Sometimes, however, individuals can be willfully and strongly tied to their own position, thus becoming entrenched (Anderson et al 1980, Anderson and Lindsay 1998, Meyer et al 2000, Locke et al 2008, Dane 2010 Dissenters must decide to either conform or remain entrenched in their view. Dissent may be sustained or increased when a dissenter thinks the decision maker is going to choose an option that the dissenter does not agree with (Che and Kartik 2009).…”
Section: Entrenchment and Dissentmentioning
confidence: 99%
“…Observing and reflecting is second nature to human beings. Reflexivity kept me engaged with the feeling of "doubt'" (Locke et al 2008), which made me engage in critical self-reflection by exploring my own interpretations of empirical material (Alvesson and Skoldberg 2000). I observed that my network connection often initially put the lower tiers in an uncomfortable position, and I found that building trust between the interviewer and interviewee was key to getting a valid and reliable account of the events being studied.…”
Section: Data Collectionmentioning
confidence: 99%